Serum oxidative markers and delta neutrophil index in hyperemesis gravidarum - Yılmaz, Gamze; Oluklu, Deniz; Şahin, Dilek; Neşelioğlu, Salim; Gök, Gamze; Erel, Özcan; Akkaya, Hatice; Özgü Erdinç, Ayşe Seval (The European Research Journal, 2024)
Objectives: To evaluate the relationship between different serum oxidative markers and the delta neutrophil index and hyperemesis gravidarum. Methods: One hundred pregnant women were enrolled in the study and divided into two groups. Group 1 included 50 women with hyperemesis gravidarum, while Group 2 (control group) included 50 pregnant women similar in age, gestational week, and body mass index. Serum oxidative markers and complete blood count inflammatory markers were compared. Results: Native thiol and total thiol were significantly lower in the Group 1 when compared with the control group (P=0.029 for native thiol; P=0.035 for total thiol). Moreover, ischemia-modified albumin (IMA) and catalase values were significantly higher in the Group 1 than in the control group (P=0.023 for IMA; P=0.021 for catalase). Index1% shows the disulfide/native thiol percent ratio and means that the Group 1 oxidant load is increased but not statistically significant. Myeloperoxidase, ferroxidase, and the delta neutrophil index did not differ significantly between the two groups (P=0.591, P=0.793, and P=0.52; respectively). Conclusions: According to our study, contrary to the literature, although there are differences in some values, when evaluated individually hyperemesis gravidarum does not impose an extra burden on maternal oxidant-antioxidant balance.